Sacred site experience : a phenomenological study - Andriotis, Konstantinos (My University, 2009)
This paper attempts to broaden the subject of sacred site experience by presenting the findings of a study on the experiences of an exclusive male sacred shrine in Greece, Mount Athos, also known as the Holy Mountain. The study involved a phenomenological approach undertaken through initiating conversations with visitors, participant observation and reviewing narratives on visitor books kept in monasteries. From the analysis five core elements of authentic experience emerged, namely spiritual; cultural; environmental; secular; and educational. These elements were discussed in relation to the methodology adopted and the findings of past research
Keywords: Religious; Christian pilgrimage; Sacred shrine; Experience; Authenticity; Phenomenology